An Analysis of Character Education Practices as Required by Curriculum 2013 in English Subject for a Pilot Public Elementary School at Jembatn Budaya School - Sukanti, A.A.I. (Universitas Pendidikan Ganesha, 2018)
This study aimed at analyzing the character education practices in an elementary school in Badung to know how the characters were designed, implemented, and assessed as well as analyzing the obstacles encountered by the teachers in integrating character values into their lessons. The data were collected through descriptive case study method involving one English teacher and 38 grade five students. The data were collected through observations, interviews, and document analysis. The findings reveal that character values were not explicitly stated in most lesson plans, however, they are detectable in integration with the learning materials, learning strategies, and learning activities. However, the implementation of the character values seemed ineffective since the focus seemed to scatter around the level of moral action and ignored the moral knowledge and feeling. This means that students were mostly told about what to do with very limited reasons and consequences of the values. It was also found that the assessment for characters was very subjective in nature, since the method used was only an observation.